Area-Based Livestock Farming: Developing Strategic Policies for Livestock Sector Development in Underdeveloped Areas - Indi Milatul Maula (Politeknik Siber Cerdika Internasional, 2025)
The development of the livestock sector in Indonesia's underdeveloped regions faces significant challenges, including limited infrastructure, inadequate access to modern technology, and weak institutional frameworks that hinder sustainable growth. One promising approach to overcoming these obstacles is the implementation of area-based livestock development, which leverages local potentials to enhance food security and improve the welfare of livestock farmers. Despite various policy efforts, most initiatives in underdeveloped livestock areas have yet to achieve optimal results, highlighting the need for more targeted and effective strategies. This study aims to formulate strategic policies that support the development of an area-based livestock sector in underdeveloped regions of Indonesia, with particular emphasis on improving food security and farmers' livelihoods. Additionally, the research explores the challenges and opportunities associated with policy implementation to provide practical recommendations for stakeholders. Employing a qualitative descriptive methodology with a case study approach, the research was conducted in selected area-based livestock zones across East Kalimantan, South Sulawesi, and West Nusa Tenggara. Data collection involved in-depth interviews, field observations, and questionnaires, which were analyzed both qualitatively and quantitatively to gain comprehensive insights. The findings indicate that area-based livestock policies have positively influenced livestock productivity and farmers’ incomes in several regions, but persistent issues related to infrastructure disparity and institutional capacity remain. The implications of this research suggest that integrated efforts involving infrastructure development, institutional strengthening, and technology adoption are crucial for the sector’s sustainability. The novelty of this study lies in its focus on region-specific policy strategies that can be tailored to local contexts. Practical recommendations include enhancing infrastructure, fostering institutional collaborations, and promoting modern technological adoption to ensure the resilience and growth of the livestock sector in underdeveloped rural Indonesia.